2020
DOI: 10.1007/s13524-019-00853-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental Involvement Laws on the Abortion Rate of Minors

Abstract: In this article, we conduct a comprehensive analysis of the effect of parental involvement (PI) laws on the incidence of abortions to minors in the United States. We contribute to the extant literature in several ways. First, we explore differences in estimates of the effect of PI laws across time that may result from changes in contraception, the composition of pregnant minors, abortion access in nearby states, and differences in how these laws are enforced. We find that PI laws enacted before the mid-1990s a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Evidence from earlier state efforts to limit minors' access to abortion showed that the distance to providers is a significant barrier. 25 For minors who need an alternative to meeting parental permission requirements, the process of obtaining a judicial bypass has become even more complicated and burdensome during the pandemic. Although most adolescents who decide to terminate their pregnancy involve a parent, 26 others fear that their parents will react with violence or kick them out of their home.…”
Section: Accepted Articlementioning
confidence: 99%
“…Evidence from earlier state efforts to limit minors' access to abortion showed that the distance to providers is a significant barrier. 25 For minors who need an alternative to meeting parental permission requirements, the process of obtaining a judicial bypass has become even more complicated and burdensome during the pandemic. Although most adolescents who decide to terminate their pregnancy involve a parent, 26 others fear that their parents will react with violence or kick them out of their home.…”
Section: Accepted Articlementioning
confidence: 99%
“…An extensive economics literature credibly exploiting natural experiments indicates that the liberalization of abortion policies in the 1960s and 1970s had profound effects in reducing fertility and delaying family formation (Angrist and Evans, 2001;Myers, 2017) and likely influenced socioeconomic outcomes for women and children (Gruber et al, 1999;Angrist and Evans, 2001;Kalist, 2004;Ananat et al, 2007). The economics literature indicates that in the fifty years since Roe, abortion and birth outcomes have been influenced by demand-side restrictions requiring parental involvement for minors seeking abortions (Levine, 2003;Joyce and Kaestner, 2020;Myers and Ladd, 2020) and mandatory waiting periods for abortions (Joyce et al, 1997;Joyce and Kaestner, 2001;Joyce et al, 2006;Lindo and Pineda-Torres, 2019;Myers, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive analysis of the effect of parental involvement (PI) laws on the incidence of abortions to minors in the United States showed that PI laws, enacted before the mid-1990s are associated with a 15% to 20% reduction in abortions to minors. However, after this time, the adoption of PI laws had little effect, on average, on abortions to minors (18).…”
Section: Factors In Favor Of Mandatory Parental Involvementmentioning
confidence: 93%